Dimensi Filosofis Ibadah Haji dan Umroh sebagai Penguat Gairah Beribadah (Pusat Riset dan Inovasi Nasional, 2024)
Hajj and Umrah are forms of maḥḍah worship that hold an essential position in Islamic teachings and contain profound philosophical dimensions. Beyond their ritual obligations and recommendations, these acts of worship function as instruments for spiritual, moral, and social development among Muslims. This study aims to analyze the philosophical dimensions of Hajj and Umrah and their implications for enhancing religious devotion. The research employs a qualitative approach with a descriptive method through library research. Data were collected from scholarly books, academic journal articles, and relevant official documents, and analyzed using content analysis. The findings indicate that Hajj and Umrah embody core values such as monotheism, sincerity, patience, self-control, equality, and social solidarity. A deep understanding of these philosophical dimensions contributes significantly to the spiritual transformation of pilgrims, as reflected in improved quality of worship, religious discipline, and social awareness after the pilgrimage. This study emphasizes that philosophical comprehension of Hajj and Umrah is crucial for sustaining long-term religious devotion among Muslims.